Assessing the impact of official development assistance on primary school performance in Côte d'Ivoire: An econometric analysis - Felix Fofana N'Zue (International Journal of Management, Economics and Social Sciences (IJMESS), 2025)
Despite the benefits of education, the learning crisis in the developing world has led the World bank to characterize it as learning poverty. Education is yet to be declared a political priority in most developing countries. Official Development Assistance (ODA), which is a mechanism for financial support from governments and their agencies to developing countries and territories, for primary education could improve education quality. This study investigates the relationship between ODA to primary education, political stability, teacher-pupil ratio, government education expenditure, and primary school performance in Côte d'Ivoire. The study uses data from the World Development Indicators and World Governance Indicators databases for the years 2002-2021. The time series characteristics of the data were ascertained and the long-run dynamics among the variables were investigated. The findings suggest that ODA has a significant negative long-run impact on primary school performance. Teacherpupil ratio and changes in political stability also have a negative impact. Government education expenditure has an insignificant impact. However, in the short-run, teacher-pupil ratio and Government education expenditure have negative and significant impact on primary school performance. The study highlights the need for efficient aid allocation, optimal teacher deployment, and stable policy environments to enhance primary education performance.
Keywords: O11; O15; I22; 330; Official development assistance; primary education; Côte d'Ivoire; ARDL model; education outcomes